An investigation into loan loss provisioning practices at U.S. bank holding companies and the impact of corporate governance mechanisms - Pilava, Andrea (2019)
Loan loss provisions in banks are set aside to face a future deterioration of credit portfolio quality and areone of the main accrual expenses for banks. In the United States, the estimation of loan loss provisions is governed by the Generally Accepted Accounting Principles which have been a target for criticism by regulators, governments and academics. This thesis examines the two main caveats of these accounting standards; the discretion embedded in the estimation and timing of certain loan losses and the inherent procyclicality of loan loss provisions as their implications can damage shareholder value and compromise the ability of banks to absorb expected credit losses. Pertaining to the discretion bank managers can exercise over the estimation and timing of loan losses, the thesis re-examines the hypotheses of prior research which postulate that loan loss provisions are affected by income smoothing, capital management and signalling incentives. In addition, motivated by current debates, the thesis also investigates whether loan loss provisions are procyclical; banks delay provisioning for bad loans until too late when a cyclical downturn has already set in, thereby magnifying the impact of the economic cycle on banks’ income and capital. The thesis implements a dynamic generalised method of moments estimator in a panel of 675 publicly traded U.S. bank holding companies over a period from 2002 to 2016-to account for unobserved heterogeneity and endogeneity-evidence in support of procyclicality, earnings management, capital management and signalling is found.